Peningkatan Aktivitas Belajar Peserta Didik Dalam Pembelajaran Agama Islam Melalui Media Animasi Berbantuan Aplikasi Canva - Maria, Anly; Cahya, Annisa; Abdullah, Deba Muslim (STAI Al-Musaddadiyah Garut, 2024)
This research discusses increasing students' learning activities in learning about Islam through animation media assisted by the Canva application. Learning activities are activities that require students to play an active role in the learning process. However, in reality, students' learning activities are currently still relatively low. This is proven by the results of observations which show that only around 35% of the 30 students can be said to be effective in learning activities so that a learning stimulus is needed, one of which is using learning media, namely animation media which can be created through the Canva application. Canva is one of the many applications that can be used to design learning media, including animation media, in which there are lots of templates available that can be used easily. The aim of this research is to describe the significance of the use of animation media assisted by the Canva application to increase students' learning activities in Islamic religious learning. This research uses a type of Classroom Action Research (CAR) or often called CAR (Classroom Action Research). Data collection techniques include observation, questionnaires, interviews and documentation. The data analysis technique uses statistical analysis techniques, in PTK only uses simple statistical formulas to find the average value and percentage of learning completeness. Based on the results of classroom action research carried out in two cycles, there was an increase in learning activities in cycle I to 57%, then there was an increase again in cycle II to 86%. Thus, it can be understood that there is a significant increase in student learning activities of 22% from pre-cycle to cycle I and 29% from cycle I to cycle II. So, overall there was an increase in student learning activities with a significance of 51% from pre-cycle to cycle II. Keywords: Learning Activities, Animation Media, Islamic Religion Instruction.